Co-creation Approach in Practice: Naming a Cafe Located within a Rural Health Service Provides Added Value to a Health Strategy. (20th March 2023) - Vargas, Carmen; Hargous, Carolina Venegas; Harfield, Janine; Bell, Colin; Whelan, Jillian
Abstract : Objective . The Victorian Government in Australia has developed Healthy Choices guidelines to ensure that healthy foods and drinks are offered and promoted in places such as hospitals. This brief report aims to present complex theoretical attributes related to cocreation through an accessible example of a competition to create a new name for the previously understated hospital "kiosk." Methods . A mixed-methods approach using an online survey and semistructured interviews were used to obtain detailed insights from hospital staff members to engage in a naming competition for a hospital-based cafe. Results . The level of engagement in this activity was higher than anticipated by the management staff. Conclusions . Active involvement of staff members through a cocreation process can enable the development of innovative healthy eating strategies and increase staff engagement to further changes in the cafe. Implications for public health cocreation in public health promises effective stakeholder engagement and requires significant scientific advancement. This brief report illustrates theoretical constructs of cocreation through a naming competition activity that occurred as part of a larger project to improve Wimmera Base Hospital's food environment.